The slant asymptote gives you linear function which is neither parallel to X-axis nor parallel to Y-axis. Since it is a linear function so its degree is 1.The another name of the slant asymptote is an Oblique asymptote .
The oblique asymptote always occurs in a rational function. It occurs when there is no horizontal asymptote.

Steps to find slant asymptote

1) Write the given equation in y = form.
2) In a rational function $f(x)=\frac{p(x)}{q(x)}$, the highest exponent of the polynomial p(x) (numerator) is 1 more than the highest exponent of the polynomial q(x) denominator.Then the function has an oblique asymptote.
Degree of p(x) > Degree of q(x) (by 1)
3) An oblique asymptote can be found out either by long division or by synthetic division. Example : If the degree of p(x) is 3 and the degree of the q(x) is 2 then you have an oblique asymptote. The degree of an oblique asymptote is 1. Examples :
1) Find the oblique asymptote of the rational function
$f(x)=\frac{x^2-x-6}{x+1}$ Solution : Write the given equation in y = form.
$y=\frac{x^2-x-6}{x+1}$
Here p(x) = $x^{2}$-x-6 with degree 2.
q(x) = x+1 with degree 1.
Degree of p(x) > Degree of q(x) (by 1) so there is a oblique asymptote
Now we will divide p(x) by q(x) using long division.

$y=(x-2)+\frac{-4}{x^2-x-6}$
So the oblique asymptote : y=x-2

2) Find the slant asymptote of the rational function
$f(x)=\frac{x^2+3x+2}{x-2}$ Solution : Write the given equation in y = form.
$y=\frac{x^2+3x+2}{x-2}$
Here p(x) = $x^{2}$+3x+2 with degree 2.
q(x) = x-2 with degree 1.
Degree of p(x) > Degree of q(x) (by 1) so there is a oblique asymptote
Now we will divide p(x) by q(x) using synthetic division.
x-2= 0
∴ x= 0

$y=(x+5)+\frac{12}{x^2+3x+2}$
So the oblique asymptote : y=x+5

3) Find the oblique asymptote of the rational function
$f(x)=\frac{3x^2+3x+1}{x+2}$ Solution : Write the given equation in y = form.
$y=\frac{3x^2+3x+1}{x+2}$
Here p(x) = $3x^{2}$+3x+1 with degree 2.
q(x) = x+2 with degree 1.
Degree of p(x) > Degree of q(x) (by 1) so there is a oblique asymptote
By doing the long division we will get
$y=(3x-3)+\frac{7}{3x^2+3x+1}$
So the oblique asymptote : y=3x-3

4)Find the oblique asymptote of the rational function $f(x)=\frac{(x+1)(x-4)}{x}$ Solution : Write the given equation in y = form.
$y=\frac{(x+1)(x-4)}{x}$
If we multiply the numerator we will get $x^{2}$-3x-4
Here p(x) = $x^{2}$-3x-4 with degree 2.
q(x) = x with degree 1.
Degree of p(x) > Degree of q(x) (by 1) so there is a oblique asymptote
By doing the long division we will get
$y=(x-3)+\frac{-4}{x^2-3x-4}$
So the oblique asymptote : y=x-3